KAJIAN FERMENTASI KACANG TANAH DARI HASIL EKSTRAKSI MINYAK DENGAN CARA PENGEMPAAN - Enny Karti Basuki Susiloningsih; Titi Susilowati (Caraka Tani: Journal of Sustainable Agriculture, 2008)
Research on changes in physico-chemical and functional properties of flour partially defatted peanut with R. oligosporus and R. oryzae were conducted. Before fermentation hull peanut was extracting the oil by hydraulic press. The experiment was arranged in completely randomized design in two times, treatment consisted of five fermentation duration (0, 8, 20, 22 and 24 hours) and two starter (R. oligosporus and R. oryzae). The result showed that R. oryzae grow faster than R. oligosporus and has gray black mycellium. Optimum time fermentations was 22 hours and fermented peanut flour by R. oligosporus has physico-chemical and functional properties better than R. oryzae.